Diseño de un centro deportivo sostenible en el espacio público en la ciudadela Ángel Escobar, cantón Otavalo - Guamán Coello, Josué David (2023)
This curricular integration work plan is developed in Otavalo city, Imbabura Province, where it is possible to propose a solution to the deficiency of green and sports areas within the city. The public space is part of the context where the architectural proposal is going to be carried out, it is necessary to carry out a previous study, to later establish a proposal that improves the quality of life of the residents and visitors to the sector. The proposal of a sports center is generated due to the absence of spaces dedicated to sports, recreation and the deficiency of quality public space, which provides users with the ability to develop activities in the urban environment.